Loans on sale: Credit market seasonality, borrower need, and lender rents - Justin Murfin; Mitchell Petersen (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2015)
The market for corporate credit is characterized by significant seasonal variation, both in interest rates and the volume of new lending. Firms borrowing from banks during seasonal "sales" in late spring and fall issue at 19 basis points cheaper than winter and summer borrowers. Issuers during cheap seasons appear to have less immediate needs, but are enticed by low rates to engage in precautionary borrowing. High interest rate periods capture borrowers with unanticipated, non-deferrable investment needs. Consistent with models of intertemporal price discrimination, seasonality is strongly associated with market concentration among a few large banks with repeated interactions.
Keywords: 330